1989
DOI: 10.1037/0735-7044.103.5.944
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and neural characteristics of short-latency and long-latency conditioned responses in cats.

Abstract: Head movements to the conditioned stimulus (a tone CS to the left ear) were studied in 6 cats. An attempt was made to differentiate an orienting, short-latency (alpha) response from the long-latency conditioned (delayed) response. The unconditioned stimulus (UCS) was a brain stimulation to the lateral hypothalamus eliciting, in addition to orienting and approach behavior, a specific, stereotypical head movement. These behavioral characteristics of the unconditioned head movement were used for differentiating i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The OR itself is also able to affect a process mediating stimulus significance, that is, associative learning. Korhonen & Penttonen (1989a, 1989b found that when unpaired presentations of a conditioned stimulus (CS) and unconditioned stimulus (US) preceded their forward pairings in one group of cats, learning was much slower than in another group of animals in which the experiment started with forwardly paired trials. A stronger OR to novel CSs when the experiment started with forward CS-US pairings was interpreted to result in faster learning.…”
Section: Orienting and Habituationmentioning
confidence: 99%
“…The OR itself is also able to affect a process mediating stimulus significance, that is, associative learning. Korhonen & Penttonen (1989a, 1989b found that when unpaired presentations of a conditioned stimulus (CS) and unconditioned stimulus (US) preceded their forward pairings in one group of cats, learning was much slower than in another group of animals in which the experiment started with forwardly paired trials. A stronger OR to novel CSs when the experiment started with forward CS-US pairings was interpreted to result in faster learning.…”
Section: Orienting and Habituationmentioning
confidence: 99%
“…In previous studies, cats showed a persistent tendency to turn their heads toward the source of the tone when the tone CS was presented to one ear and paired with electrical stimulation of the medial forebrain bundle (MFB) in the lateral hypothalamus (Korhonen & Penttonen, 1989a, 1989b. These head-turn CRs disappeared during subsequent unpaired presentations of the CS and US.…”
mentioning
confidence: 97%
“…Electrical stimulation (unconditioned stimulus, or US) is applied to the medial forebrain bundle at the level of the lateral hypothalamus. The amplitude of the head turn (conditioned response, or CR) is then measured with a movement acceleration transducer attached to the eat's head during paired (Korhonen & Penttonen, 1989) and differential (Penttonen, Korhonen, Arikoski, & Hugdahl, 1993) conditioning. The qualitative features of the CR are observed from videorecordings, and this process is guided by the trial information superimposed on the animal's behavior by the experiment control system.…”
Section: Application Examplesmentioning
confidence: 99%